2015
DOI: 10.1007/s00330-015-3935-5
|View full text |Cite
|
Sign up to set email alerts
|

Which factors influence MRI-pathology concordance of tumour size measurements in breast cancer?

Abstract: • Execution and scope of MRI and histopathological size measurements influence concordance rate. • Non-mass like enhancement predicts discordance. • Additional high-risk lesions in proximity of tumour do not cause measurement discordance. • Low percentage of ILC do not enhance at all.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 39 publications
3
39
1
2
Order By: Relevance
“…In our sample population MRI overestimated the pathology size in 24% of the cases, which is consistent with the literature, ranging from 6% to 81% [2,10]. However, it should be remembered that for TNM classification, pathologists consider just the invasive component size of the tumor, while it is well established that MRI measurement includes both invasive and noninvasive components [5,11,12].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In our sample population MRI overestimated the pathology size in 24% of the cases, which is consistent with the literature, ranging from 6% to 81% [2,10]. However, it should be remembered that for TNM classification, pathologists consider just the invasive component size of the tumor, while it is well established that MRI measurement includes both invasive and noninvasive components [5,11,12].…”
Section: Discussionsupporting
confidence: 90%
“…Recent studies have suggested that MRI is superior to mammography and ultrasound in determining invasive tumor size, depicting multifocality, as well as evaluating the intraductal component [1][2][3][4][5]9] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations